Central Nervous System Regulation of Intestinal Lipoprotein Metabolism by Glucagon-Like Peptide-1 via a Brain–Gut Axis. Issue 5 (May 2015) - Farr, Sarah; Baker, Christopher; Naples, Mark; Taher, Jennifer; Iqbal, Jahangir; Hussain, Mahmood; Adeli, Khosrow
Abstract : Objective—: Intestinal overproduction of atherogenic chylomicron particles postprandially is an important component of diabetic dyslipidemia in insulin-resistant states. In addition to enhancing insulin secretion, peripheral glucagon-like peptide-1 (GLP-1) receptor stimulation has the added benefit of reducing this chylomicron overproduction in patients with type 2 diabetes mellitus. Given the presence of central GLP-1 receptors and GLP-1–producing neurons, we assessed whether central GLP-1 exerts an integral layer of neuronal control during the production of these potentially atherogenic particles. Approach and Results—: Postprandial production of triglyceride-rich lipoproteins was assessed in Syrian hamsters administered a single intracerebroventricular injection of the GLP-1 receptor agonist exendin-4. Intracerebroventricular exendin-4 reduced triglyceride-rich lipoprotein-triglyceride and -apolipoprotein B48 accumulation relative to vehicle-treated controls. This was mirrored by intracerebroventricular MK-0626, an inhibitor of endogenous GLP-1 degradation, and prevented by central exendin9–39, a GLP-1 receptor antagonist. The effects of intracerebroventricular exendin-4 were also lost during peripheral adrenergic receptor and central melanocortin-4 receptor inhibition, achieved using intravenous propranolol and phentolamine and intracerebroventricular HS014, respectively. However, central exendin9–39 did not preclude the effects of peripheral exendin-4 treatment on chylomicron output. Conclusions—: Central GLP-1 is a novel regulator of chylomicron production via melanocortin-4 receptors. Our findings point to the relative importance of central accessibility of GLP-1–based therapies and compel further studies examining the status of this brain–gut axis in the development of diabetic dyslipidemia and chylomicron overproduction. Abstract : Supplemental Digital Content is available in the text.